Työvoimatutkimus 1983, 2. neljännes - (:unkn) unknown (Tilastokeskus, 1983)
Liite: Korjattuja tuloksia vuodelta 1982
Arbetskraftsundersökningen 1983, 2. kvartalet
Keywords: tilastot; työmarkkinat; työvoima; työllisyys; työttömyys; Työmarkkinat; Työtilastot, työmarkkinat ja työssäkäynti